Institute for Clinical and Economic Review - Peterson Health Technology Institute value assessment framework for digital health technologies - Steven D Pearson; Prabhjot Singh; Francesca Beaudoin; Jon Campbell; Lindsey Schapiro; Sarah K Emond; Caroline Pearson (Becaris Publishing Limited, 2023)
Digital health technologies (DHTs) are a broad and rapidly innovating class of interventions with distinctive pathways for development, regulatory approval, uptake and reimbursement. Given the unique nature of DHTs, existing value assessment frameworks and evidence standards for health technologies such as drugs and devices are not directly applicable. The value assessment framework presented here describes a conceptual model and associated methods to guide assessments of DHTs. The framework seeks to accomplish two goals: to set evidence standards that guide technology developers to generate robust evidence on their products; and to provide reviews that help organizations adopt high-impact DHTs with the strongest evidence for delivering improved clinical outcomes and cost savings. This assessment framework will serve as the roadmap for future evaluations of DHTs by the Institute for Clinical and Economic Review (ICER) and the Peterson Health Technology Institute (PHTI). We believe that all stakeholders will benefit from comprehensive and explicit standards of evidence on the different dimensions necessary to understand the value of DHTs.